The gravity of academic plagiarism in the perception of scholars, students, and science policy makers in Bulgaria - Vassileva, Irena; Yankova, Diana; Chankova, Mariya (English Studies at NBU, 2025)
The ever-increasing spread of plagiarism in academia requires development of strategies to combat it so as to increase the prestige of Bulgarian scholars at the international and local level. Therefore, the main goals of the project are to analyze the concept of plagiarism in academia, arriving at a clear and detailed definition, applicable in practice to create efficient methods to combat it, and to investigate its understanding by students, scholars and science managers to establish the discrepancies between the nature of plagiarism and its perception in the Bulgarian academic community. Expected results: (1) Theoretical – elicitation of a definition of plagiarism; drafting of comprehensive legal and administrative approaches to combat plagiarism; design of a sociological methodology for a study of the problem. (2) Applied - transfer of knowledge; creating guidelines for combating plagiarism; raising the awareness of Bulgarian academe about the severity of plagiarism as a violation of academic ethics.